2017
DOI: 10.1007/s00442-017-3973-6
|View full text |Cite
|
Sign up to set email alerts
|

Water availability and environmental temperature correlate with geographic variation in water balance in common lizards

Abstract: Water conservation strategies are well documented in species living in water-limited environments, but physiological adaptations to water availability in temperate climate environments are still relatively overlooked. Yet, temperate species are facing more frequent and intense droughts as a result of climate change. Here, we examined variation in field hydration state (plasma osmolality) and standardized evaporative water loss rate (SEWL) of adult male and pregnant female common lizards (Zootoca vivipara) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 67 publications
3
49
0
Order By: Relevance
“…Interestingly, behavioral adjustments were not efficient enough to counter physiological dehydration since lizards in this study suffered from a slight increase in plasma osmolality and decrease in body mass change as in earlier laboratory experiments (Dupoué et al 2018). The range of measured changes in plasma osmolality in this study indicates a mild physiological dehydration (Dupoué et al 2018), and plasma osmolality levels of water-restricted individuals were high compared to baseline levels recorded in a range of natural populations with contrasted access to water (Dupoué et al 2017). In addition, we found gradual changes in behavioral responses of lizards in this experiment, which suggests that they are mostly driven by changes in water balance instead of a direct response to water availability per se.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Interestingly, behavioral adjustments were not efficient enough to counter physiological dehydration since lizards in this study suffered from a slight increase in plasma osmolality and decrease in body mass change as in earlier laboratory experiments (Dupoué et al 2018). The range of measured changes in plasma osmolality in this study indicates a mild physiological dehydration (Dupoué et al 2018), and plasma osmolality levels of water-restricted individuals were high compared to baseline levels recorded in a range of natural populations with contrasted access to water (Dupoué et al 2017). In addition, we found gradual changes in behavioral responses of lizards in this experiment, which suggests that they are mostly driven by changes in water balance instead of a direct response to water availability per se.…”
Section: Discussionsupporting
confidence: 46%
“…In this study, we used a laboratory experiment to quantify the behavioral responses to a chronic water restriction and acute heat stress in the European common lizard Zootoca vivipara . This cold‐adapted species inhabits mesic environment and is tightly dependent on humid conditions in the wild (Lorenzon et al , Massot et al , Dupoué et al ). In previous studies, we have shown that common lizards exposed to dry soil conditions invest more in exploration behaviors (Rozen‐Rechels et al ), and juvenile lizards living in dry habitats disperse more from their natal home range (Massot et al ), whereas sub‐adults reduce their locomotor activity during a chronic water restriction (Lorenzon et al ).…”
Section: Introductionmentioning
confidence: 99%
“…We first investigated how oxidative status relates to reproduction and environmental conditions in natural populations using a ‘cross‐sectional study’. We compared variation in oxidative status among pregnant females and adult males from 12 natural populations distributed across a gradient of air temperature and water availability (permanent in humid peat bogs vs. periodic in dry meadows, Dupoué, Rutschmann, Le Galliard, Miles, et al, ; Dupoué, Rutschmann, et al, ). We subsequently examined the effects of water restriction on oxidative status in pregnant females and adult males, and reproductive effort in females using an ‘experimental study’.…”
Section: Introductionmentioning
confidence: 99%
“…We induced a two‐week period of water restriction during pregnancy, a protocol known to trigger hydric costs of reproduction and mother–offspring conflict for water (Dupoué, Le Galliard, et al, ). An important aspect of the studied populations is that all adult females engage in reproduction so that we cannot quantify the cost of pregnancy (Dupoué, Rutschmann, Le Galliard, Miles, et al, ). That is, reproductive female Z. vivipara commit energy to a litter prior to fertilization.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we examined the variation in baseline plasma corticosterone (the primary GCs in birds and reptiles) across 14 populations of the European common lizard (Zootoca vivipara) distributed across an altitudinal gradient. Our study populations occupy habitats that differ in thermal microclimates and access to free-standing water (Dupoué, Rutschmann, Le Galliard, Miles, et al, 2017;Rutschmann et al, 2016), and are distributed along an extinction risk gradient including rapidly declining populations at the lowest altitudes and steady populations at mountaintops (Chamaillé-Jammes, Massot, Aragon, & Clobert, 2006;Sinervo et al, 2010). So far, population extinction has been directly related to warmer conditions in lowland populations although the proximate mechanisms remain unknown (Bestion, Teyssier, Richard, Clobert, & Cote, 2015).…”
Section: Introductionmentioning
confidence: 99%